Interaction of mechanical and thermal lesions induced by high intensity focused ultrasound (HIFU) - Gao, Xiaobin (2014)
High-intensity focused ultrasound (HIFU) is emerging as an effective therapeutic modality in both thermal ablation for solid tumor/cancer therapy and soft-tissue fragmentation. Mechanical as well as thermal effects play an important role in the HIFU treatment simultaneously. Further understanding the underlying mechanisms of HIFU ablation is critical for its safety and efficiency in the clinical application as well as developing new technology. In order to achieve our goals, nonlinear acoustic propagation of a HIFU burst was first simulated using KZK equation. Then bubble dynamics at the focal plane of the HIFU transducer, where a soft tissue is located, was simulated by the Gilmore model and its diffusion in the interval time by a static diffusion model with the progress of HIFU ablation. The simulation results show that the bubble dynamics is not consistent for each burst exposure and in general the maximum bubble size reached and the associated radiation acoustic pressure in the collapse increase with the number of delivered bursts although there are significant variations. This finding has a good agreement with the erosion on the soft tissue during histotripsy, starting at the focus, extending laterally and then reaching the threshold for the erosion area. Secondly, a novel lesion production strategy was developed and tested in both gel phantom and ex vivo tissue with the HIFU pulse duration much longer than that of histotripsy but shorter than boiling histotripsy. The characteristics of bubble cavitation by passive cavitation detection (PCD) for the inertial and stable cavitation and temperature elevation by a thermocouple were measured during the therapeutic procedure. Lesion would vary from a mechanical erosion in the shape of a “squid” to a “dumbbell” lesion with